The Self-Control In Mediating The Relationship Between Financial Literacy And Digital Financial Inclusion With The Financial Management Behavior Of Generation Z - Putri Ayunda Anggraeni; Detak Prapanca; Herlinda Maya Kumala Sari (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study aims to examine the influence of financial literacy, digital financial inclusion, and self-control on financial management behavior among Generation Z, as well as to analyze the role of self-control as an intervening variable. This research employs a quantitative approach using a survei method by distributing questionnaires to 120 Generation Z respondents who actively engage in digital financial activites. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The resluts show that digital financial inclusion and self-control have a positive and significant effect on financial management behavior. In addition, financial literacy and digital financial inclusion have a positive and significant effect on self-control. However, financial literacy does not have a significant effect on financial management behavior, indicating that financial knowledge alone is not sufficient to drive behavioral changes without internal motivation or habitual application in daily life. Self-control also fails to mediate the effect of financial literacy and digital financial inclusion on financial management behavior. These findings suggest that financial education should not only focus on cognitive aspects but also emphasize character building and the development of positive habits from an early age in order to foster healthy and sustainable financial bahevior.